We want a living wage”: the impact of the national minimum wage on struggles of domestic workers in South Africa - Cabe, Musawenkosi (University of the Witwatersrand, Johannesburg, 2024)
In 2018, the South African government introduced the National Minimum Wage (NMW) Act as a structured policy intervention to address the high levels of working poverty and income inequality. Economic models projected that a NMW set at R3 500 a month would raise the incomes of almost half of South Africa’s workforce (Finn, 2015; Isaacs, 2016). However, a study commissioned by the National Minimum Wage Commission post-implementation, observed only a moderate increase in wages and a limited effect on the wage distribution. The “muted” impact of the NMW was attributed primarily to high levels of non-compliance, a lack of knowledge by employers and weak enforcement. Drawing on semi-structured interviews with domestic workers, employers and domestic workers organisations in Gauteng Province, this research report explores: How familiar are workers and employers with the NMW? How does the intimate nature of domestic work influence the possibilities of its enforcement? How have domestic workers leveraged the NMW, individually and collectively, to secure better working conditions? How can the South African case inform global campaigns to improve the conditions of work among domestic workers? The findings suggest that although the uptake was gradual because of the initial phase-in period, the NMW had a positive impact on the wages of domestic workers who participated in the research. There is a general awareness from employers and domestic workers of the NMW and, with the exception of one respondent, all domestic workers earned at least the NMW. However, domestic workers also noted that the NMW was too low and that given the high cost of living, they were not able to meet their basic needs. Therefore, domestic workers cultivate affective relationships with employers to secure benefits beyond the wage. However, affect is a double-edged sword which can be used by employers to extract additional work from domestic workers. Despite its limitations, the NMW has served as an anchor of recruitment and mobilisation for domestic workers unions and organisations, with some positive results as we saw with One-Wage-Campaign. However, as the South African case shows, the NMW alone cannot address the problem of poverty and inequality. The introduction of a NMW must be complemented by other social policy measures such as a Universal Basic Income Guarantee (UBIG), free public services, subsidised transport, and housing.
A Research Report submitted in partial fulfillment of the Degree of Masters of Commerce (Inequality Studies) in the School of Economics and Finance University of the Witwatersrand, Johannesburg, 2024
Keywords: national minimum wage; paid domestic work; enforcement; agency; unions; SDG-8: Decent work and economic growth